2006
DOI: 10.1104/pp.105.074898
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Hsa32, a Novel Heat Shock Protein, Is Essential for Acquired Thermotolerance during Long Recovery after Acclimation

Abstract: Plants and animals share similar mechanisms in the heat shock (HS) response, such as synthesis of the conserved HS proteins (Hsps). However, because plants are confined to a growing environment, in general they require unique features to cope with heat stress. Here, we report on the analysis of the function of a novel Hsp, heat-stress-associated 32-kD protein (Hsa32), which is highly conserved in land plants but absent in most other organisms. The gene responds to HS at the transcriptional level in moss (Physc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
225
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(244 citation statements)
references
References 41 publications
12
225
1
Order By: Relevance
“…The Arabidopsis (Arabidopsis thaliana) T-DNA KO mutants hsp101, hot1-3, and hsa32-1 were as described previously (Lee et al, 2005;Charng et al, 2006). The double KO mutant hsp101 hsa32-1 was generated by crossing the single mutant lines and isolated from the offspring in the F2 generation.…”
Section: Plants Materials and Mutant Screenmentioning
confidence: 99%
See 1 more Smart Citation
“…The Arabidopsis (Arabidopsis thaliana) T-DNA KO mutants hsp101, hot1-3, and hsa32-1 were as described previously (Lee et al, 2005;Charng et al, 2006). The double KO mutant hsp101 hsa32-1 was generated by crossing the single mutant lines and isolated from the offspring in the F2 generation.…”
Section: Plants Materials and Mutant Screenmentioning
confidence: 99%
“…However, just how plants keep the memory of heat acclimation is not clear. Our previous studies suggest that a heat-induced 32-kD protein, HSA32, is involved in prolonging the memory of heat acclimation in Arabidopsis (Arabidopsis thaliana; Charng et al, 2006). HSA32 is not a canonical heat shock protein (HSP).…”
mentioning
confidence: 99%
“…Acquisition of thermotolerance has been found to be negatively affected in Hsp70 antisense A. thaliana plants ( Lee and Schoffl, 1996). Hsa32 in A. thaliana is heat-inducible protein (Charng et al, 2006). Mutant/ RNAi plants lacking Hsa32 do not survive a severe HS treatment even after a pre-treatment at a sublethal temperature (Charng et al, 2006).…”
Section: High Temperature Tolerant Transgenics Raised Through Alterinmentioning
confidence: 99%
“…Hsa32 in A. thaliana is heat-inducible protein (Charng et al, 2006). Mutant/ RNAi plants lacking Hsa32 do not survive a severe HS treatment even after a pre-treatment at a sublethal temperature (Charng et al, 2006). Very recently, Charng et al (2007) have shown that HsfA2 (heat-inducible trans-activator protein which sustains the expression of Hsp genes and prolongs the acquired thermotolerance in A. thaliana) under-expression results in an increased sensitivity of the mutant plants to HS.…”
Section: High Temperature Tolerant Transgenics Raised Through Alterinmentioning
confidence: 99%
“…HSFA3 plays a key role in expression of many HSP genes, gene products of which contribute to either positive or negative feedback of heat stress responses and eventually provides efficient plant heat stress adaptation (Charng et al, 2006). Because mature mRNA expression of HSFA3 correlated well with plant heat tolerance in our two-step acquired heat assay, we further examined whether HSFA3 could drive plant heat stress tolerance for itself downstream of STA1.…”
Section: Reconstitution Of Heat-inducible Transcription Cascades By Dmentioning
confidence: 99%